Author Correction: Deep Learning and Radiomics predict complete response after neo-adjuvant chemoradiation for locally advanced rectal cancer. Issue 1 (December 2018) - Bibault, Jean-Emmanuel; Giraud, Philippe; Housset, Martin; Durdux, Catherine; Taieb, Julien; Berger, Anne; Coriat, Romain; Chaussade, Stanislas; Dousset, Bertrand; Nordlinger, Bernard; Burgun, Anita
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.